An application of the error correction model in analyzing the long run equilibrium between Ghana’s exports and imports - Acquah, Henry de-Graft; Acquah, Joyce De-Graft (Applied Studies in Agribusiness and Commerce, 2015)
This study investigates the long-run relationship between Ghana’s exports and imports for the period of 1948 to 2012. Using the Engle Granger two-step procedure we find that Ghana’s exports and imports are cointegrated. However, the slope coefficients from the cointegration equations were not statistically equal to 1. Furthermore, application of the error correction model reveals that 1% increase in the imports will significantly result in 0.56% increase in exports, suggesting that the exports’ responsiveness to imports is low. The estimated error correction coefficient suggests that 32% of the deviation from the long run equilibrium relation is eliminated, leaving 68% to persist into the next period. These results suggest persistence in the trade deficit and an option of curbing the deficit is to re-order the relationship between imports and exports with a view to reducing imports demand. These results imply that though Ghana’s past macroeconomic policies have been effective in bringing its imports and exports into a long run equilibrium, it is yet to satisfy the sufficient condition for sustainability of foreign deficit.